Dried small fish provide nutrient densities important for the first 1000 days. Issue 4 (4th May 2021) - Byrd, Kendra A.; Pincus, Lauren; Pasqualino, Monica M.; Muzofa, Farayi; Cole, Steven M.
Abstract: Inadequate nutrient intakes are prevalent among many populations in sub‐Saharan Africa and increasing fish consumption among pregnant/lactating women and children is one strategy to improve diets and address nutrient deficiencies. We report the nutrient content of two fish‐based recipes—fish powder and fish chutney—that contain dried small fish available in local markets in Zambia. The contribution of a serving of each recipe to the recommended daily intakes of iron, zinc, calcium and docosahexaenoic acid (DHA) for pregnant/lactating women and children 6–24 months was calculated because these nutrients are commonly deficient in African diets. We found that one 10‐g serving of fish powder provides 20% or more of the daily calcium recommendation and 37% or more of the daily DHA recommendation for both pregnant/lactating women and children. A 30‐g serving of fish chutney provides over 40% of the daily calcium recommendation for pregnant women and over 50% for lactating women. Additionally, we investigated the nutrient density (nutrients per kilocalorie) of the fish powder and compared it with the nutrient density of a small‐quantity lipid‐based nutrient supplement plus (SQ‐LNS‐plus). SQ‐LNS‐plus is designed to enhance children's diets by providing micronutrients and DHA. Fish powder is similar to SQ‐LNS‐plus in iron and zinc density and even higher in calcium and DHA density. Consuming dried small fish as part of a daily meal can be a viable strategy for combatting nutrient deficiencies in the first 1000 days.